SUATU TINJAUAN PERTANGGUNG JAWABAN PIDANA TERHADAP PELAKU TINDAK PIDANA MEMBUANG ANAK (TOVENDELING KEEGEN) BERDASARKAN PASAL 305, 306, 307 dan 308 KUHP - Robiansyah, Muhamad (Journal of Law ( Jurnal Ilmu Hukum ), 2018)
ABSTRACTÂ National development which is a process of modernization has both positive and negative impacts, many events that have attracted public attention these days. The increasing number of criminal acts, delicacy (delinquency) of children and the emergence of crime problems against children even throw away their own children. The research aims to find out the criminal responsibility of the perpetrator of the crime of throwing away the child. Based on the legal material of the Biblical Criminal Law (KUHP), Law Number 23 of 2002 concerning Child Protection, Law Number 39 of 1999 concerning Human Rights. Criminal sanctions are one of the ways to cope with criminal acts, the debate over criminal planning in the face of crime, has been going on for hundreds of years, the handling of crime by imposing criminal sanctions is the oldest way. Ability to be criminally responsible in relation to one's mental / mental state. When the perpetrator takes action in a state of physical and spiritual health, so that he is not categorized as a party covered by articles 44, 48, 49, 50 and 51 of the Criminal Code (there are forgiveness and justification reasons). To cope with criminal acts of throwing children out of society, such as can be done by legal and religious counseling, especially in the community and school environment.Â Keywords: Crime of throwing children based on articles 305, 306, 307 and 308 of the Criminal Code